Factors associated with minimum dietary diversity among 6-11-month-old children in Indonesia: Analysis of the 2017 Indonesian Demographic and Health Survey - Zebadia, Eurika; Atmaka, Dominikus Raditya (Public Health and Preventive Medicine Archive, 2021)
Background and purpose: The indicators to assess food diversity in complementary feeding is minimum dietary diversity (MDD). In 2017, the proportion of MDD among 6-11-month-old children in Indonesia was 33.8%, which was the lowest among other age group and below the national rate. This study aims to explore factors associated with MDD among 6-11-month-old children in Indonesia. Methods: This study was a secondary data analysis of the 2017 Indonesia Demographic and Health Survey (IDHS), a crosssectional study involving 17,848 children across all provinces in Indonesia. The final samples included in this analysis were 1,593 children aged 6-11-month-old. Variables analyzed were parent’s education level, access to information, parent’s occupation, wealth index, and access to health facilities. Logistic regression model was applied to identify factors associated with MDD. Results: The proportion of MDD in this study was 35.1%. The highest food groups that were consumed were staple food, vitamin-A rich fruits and vegetables, and breastmilk. The final model showed factors which correlated significantly with complementary feeding practices that met MDD requirement were wealth index categorized as richer (OR=1.72; 95%CI: 1.16-2.55; p=0.007), wealth index categorized as richest (OR=2.42; 95%CI: 1.58-3.68; p<0.001) and using internet almost every day (OR=1.42; 95%CI: 1.05-1.91; p=0.023). Conclusion: Wealth index and internet use were independently associated with MDD. Online media should be considered as channel to spread information of complementary feeding diversity to children, while socio-economic factor which associated to food accessibility should be addressed by involving beyond health sector.